Determinan Factors of Decision to Choose an Online Travel Agent to Book a Place to Stay - Tiffani Dias Anggraeni; Megawati Simanjuntak; Popong Nurhayati (Jurnal Doktor Manajemen (JDM), 2023)
This study analyzes the factors influencing customers to book a place to stay through Online Travel Agent (OTA). This research was conducted on 382 respondents selected by convenience sampling with the criteria of having booked a place to stay through OTA in the last two years and being at least 18 years old. This research uses quantitative methods by filling out questionnaires distributed online. Data were analyzed using SEM AMOS. The results showed that brand image and perceived ease of use (PEU) have a significant positive direct effect on the decision to choose an OTA to book a place to stay, brand image and PEU has a significant positive indirect effect on e-WOM, e-WOM has a significant negative effect on the decision to choose OTA to book a place to stay and perceived risk does not significantly influence the decision to choose OTA to book a place to stay. The managerial implications can be carried out by company management in collaboration with OTA to increase the intention of repurchasing customers through comments (e-WOM), maintaining the privacy of customers' data to avoid leakage, improving transaction systems safety, and conducting evaluations related to quality and service.